Predictability of ASEAN-5 exchange rates in the post-crisis era - Liew, Khim Sen; Baharumshah, Ahmad Zubaidi (Universiti Putra Malaysia Press, 2003)
Five ASEAN currencies are investigated in an attempt to determine whether the post-crisis ASEAN exchange rates are more predictable by the US dollar or Japanese yen. Results suggest that prior to the 1997/1998 Financial Crisis, all exchange rates were better predicted by the US dollar as the base currency. The post-crisis Singapore exchange rate continues to be better predicted in US dollar. On the other hand,Japanese yen better predicted other post-crisis ASEAN exchange rates.